Model for effectiveness evaluation of planning measures for protection of areas surrounding main roads from the influence of environmental pressures of the Kyiv main road network - Priymachenko, Oleksiy (КНУБА, 2017)
Raising the requirements to the ecological state of the urban environment engenders the issue of efficient planning and functioning of protection elements of areas surrounding main roads. Surrounding main roads are areas situated along the main trunk road networks within the space from the main road to the building line. As defined, the building lines are the boundaries of placing houses and buildings relative to frontage lines [1]. They make up about 15 − 30 % of a town or city area [2].Research of the methodological framework of the sustainable development of urbanized territories should be based on a complex problemoriented approach of different related scientific researches. This is why the task of examining the environmental pressures of main road network is highly relevant for a city. An analysis of Ukrainian regulatory documents showed that the development and feasibility evaluation of urban development regulations are insufficient for evaluation of planning measures for protection of the areas surrounding main roads. The mathematical and information models demonstrating the dependence of environmental pressures by factors and attributes in accordance with planning decisions were presented for the evaluation. On-sight surveys of a main road network with different planning criteria were conducted as exemplified by Kyiv, in the course of which data necessary for evaluating the efficiency of planning decisions were collected. On the basis of the obtained data recommendations on planning decisions for respective urban areas have been given.
Keywords: trunk road network; environmental pressures; urban area protection.